Odontogenic cellulitis in children requiring hospitalization - Jun Kuo; Yai-Tin Lin; Yng-Tzer Joseph Lin (Elsevier, 2013)
Background/purpose: Facial cellulites are frequently seen in children's hospitals, and it can lead to complicated systemic illnesses. The purpose of this retrospective study was to investigate clinical characteristics of odontogenic facial cellulitis in children requiring hospitalization. Materials and methods: One hundred and fifty hospitalized children (75 boys and 75 girls), with an average age of 5.17±2.09 years, who were treated for odontogenic facial cellulitis at Kaohsiung Chang Gung Children Hospital, Taiwan, were selected for this study. An infectious primary lesion was identified when the infection originated from a fresh lesion of an infected tooth, compared to a secondary lesion. Study variables included age, gender, location of the cellulitis, source of the infection, length of hospitalization, and symptoms and signs of infection during the hospitalization. Results: The mean hospitalization length was 5.15±1.52 days. A greater association of upper-face infections with upper anterior teeth was found than lower anterior teeth with lower-face infections. Fever during hospitalization and the source of the infection in the anterior teeth were found to have occurred significantly more frequently with a primary than with secondary infectious lesion (P<0.05). Conclusion: Differences in upper- and lower-face infections were not clinically significant except for the source of the infection. In terms of the effects of the infectious lesion, significant differences were found between primary and secondary lesions in terms of having a fever during hospitalization and an anterior source for the infection.